Lapatinib-Loaded Nanocapsules Enhances Antitumoral Effect in Human Bladder Cancer Cell - Buss, Julieti Huch; Begnini, Karine Rech; Bruinsmann, Franciele Aline; Ceolin, Taíse; Sonego, Mariana Souza; Pohlmann, Adriana Raffin; Guterres, Sílvia Stanisçuaski; Collares, Tiago; Seixas, Fabiana Kömmling (Frontiers in Oncology, 2019)
Transitional cell carcinoma (TCC) represent the most frequent type of bladder cancer. Recently, studies have focused on molecular tumor classifications in order to diagnose tumor subtypes and predict future clinical behaviour. Increased expression of HER1 and HER2 receptors in TTC is related to advanced stage tumors. Lapatinib is an important alternative to treat tumors that presents this phenotype due to its ability to inhibit tyrosine kinase residues associated with HER1 and HER2 receptors. This study evaluated the cytotoxicity induced by LAP-loaded nanocapsules (NC-LAP) compared to LAP in HER-positive bladder cancer cell. The cytotoxicity induced by NC-LAP was evaluated through flow cytometry, clonogenic assay and RT-PCR. NC-LAP at 5uM reduced the cell viability and was able to induce G0/G1 cell cycle arrest with up-regulation of p21. Moreover, NC-LAP treatment presented significantly higher apoptotic rates than untreated cells and cells incubated with drug-unloaded nanocapsules (NC) and an increase in Bax/Bcl-2 ratio was observed in T24 cell line. Furthermore, clonogenic assay demonstrated that NC-LAP treatment eliminated almost all cells with clonogenic capacity. In conclusion, NC-LAP demonstrate antitumoral effect in HER-positive bladder cells by inducing cell cycle arrest and apoptosis exhibiting better effects compared to the non-encapsulated lapatinib. Our work suggest that the LAP loaded in nanoformulations could be a promising approach to treat tumors that presents EGFR overexpression phenotype.